Simultaneous extraction and preliminary purification of polyphenols from grape pomace using an aqueous two-phase system exposed to ultrasound irradiation: Process characterization and simulation - Xie, Guangjie; Shen, Juan; Luo, Ji; Li, Dandan; Tao, Yang; Song, Changnian; Han, Yongbin (Frontiers in Nutrition, 2022)
Ultrasound-assisted aqueous two-phase (ATP) extraction method was used for the extraction and purification of phenolic compounds from grape pomace in the present study. An aqueous two-phase system (ATPS) was established by generating a phase diagram and selecting the appropriate phase composition and concentration. Sonication was performed at different acoustic energy densities (AED, 41.1、63.5、96.1、111.2 W/L) and temperatures (20、30、40oC). Artificial neural network (ANN) was successfully used to correlate the extraction parameters with phenolic yield Then, a diffusion model based on Fick's second law was used to model the mass transfer process during ultrasound-assisted ATP extraction and evaluate the effective diffusion coefficient of phenolics. The results revealed the increase in AED and temperature increased the effective diffusivity of phenolics. The HPLC analysis of anthocyanins and flavonols showed that ultrasound significantly increased the extraction yield of anthocyanins compared with the traditional method. High amounts of rutin and myricetin were recovered using the ATPS systems. Sugars were mainly distributed in the bottom phase, whereas phenolics were located in the top phase. Overall, the simultaneous separation and preliminary purification of phenolics was achieved by the ultrasound-incorporated partitioning approach.